2023
DOI: 10.1002/hed.27357
|View full text |Cite
|
Sign up to set email alerts
|

Response to induction chemotherapy in sinonasal malignancies: A single‐institutional experience

Abstract: Background: Sinonasal malignancy (SNM) is a heterogeneous group of diseases for which induction chemotherapy (IC) may reduce tumor burden.The purpose of this study was to characterize the response to IC in SNM as a prognostic factor through its effect on survival.Methods: Retrospective cohort of patients undergoing IC for SNM between 2010 and 2019 at our quaternary referral center.Results: Forty-two patients with advanced SNM were included in the analysis.Patients with a favorable response to IC had higher sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Nyiriesy et al looked at multiple sinonasal pathologies but performed a secondary analysis of SNSCC comparing those who were treated with and without IC [38]. As expected, those treated with IC were significantly more likely to have orbital, skull base, or dural involvement as well as a higher T stage.…”
Section: Induction Chemotherapy In Sinonasal Squamous Cell Carcinomamentioning
confidence: 96%
“…Nyiriesy et al looked at multiple sinonasal pathologies but performed a secondary analysis of SNSCC comparing those who were treated with and without IC [38]. As expected, those treated with IC were significantly more likely to have orbital, skull base, or dural involvement as well as a higher T stage.…”
Section: Induction Chemotherapy In Sinonasal Squamous Cell Carcinomamentioning
confidence: 96%
“…1 These tumors tend to be aggressive and are usually diagnosed late, making treatment challenging, with oncologic outcomes for SNMs not significantly improving over the past 30 years. 2 Current treatment is guided by histology, with most SNMs benefiting from multimodal therapy and surgical resection. Obtaining negative margins during resection is critical to improving patient survival.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies have suggested that IC response could be used as a guide for SNM patient treatment and survival. 2,12 However, the use of IC is relatively novel in SNMs, with a paucity of literature on the effects of IC on orbital preservation and orbital function. In this study, we performed a systematic review of studies reporting on IC use in SNMs with orbital invasion.…”
Section: Introductionmentioning
confidence: 99%